Bio-synthesised nanoparticles employment for eliminating metals from wastewater via implementation of a three level Box-Behnken technique - P. Jyolsna; V. Gowthami; A. Hajeera Aseen (Applied Water Science)
Abstract The objective of the present study is to optimise the removal of metals such as aluminium, zinc, and copper from industrial wastewater using green-synthesised nanoadsorbents. To achieve this, the Box–Behnken experimental design and response surface methodology will be employed. We used inductively coupled plasma mass spectrometry to analyse the metals present in the wastewater. A three-factor, three-stage Box–Behnken design was used to maximise the removal of these metals from aqueous solution. This involved response surface modelling and quadratic programming based on 17 different experimental data from a batch study. The study focused on three independent variables: pH, contact time, and adsorbent amount. The nanoadsorbents were prepared using a combination of Citrus X sinensis peel and Musa Cavendish peel extract, which served as the reducing agents, to produce a combined peel extract-silver nanoparticle product. Field emission scanning electron microscopy imaging and UV–visible spectroscopic analysis unequivocally demonstrated the presence of nanoparticles, with a surface plasmon resonance at 438 nm. The optimal values of the selected variables were determined by solving the quadratic regression model and analysing the contour plots of the reaction surface. At the experimental conditions of pH = 5, contact time = 92.5 min, and adsorbent dosage = 0.1 g/L, the recovery efficiency of Al, Cu, and Zn was significantly reduced. The optimised parameters were successfully applied to wastewater collected, and the degradation of detected metal ions was tested. The experiment demonstrated an effective reduction in these metals.